Monitoring research of somatic cells count in goat milk in the eastern region of Ukraine - FOTINA, T. I.; FOTINA, H. A.; LADYKA, V. I.; LADYKA, L. M.; ZAZHARSKA, N. M. (Journal of the Hellenic Veterinary Medical Society, 2018)
The aim of research was to analyze the contents of somatic cells (SC) in goat milk in the East of Ukraine, level of SC translocation in the process of milking, speed of SC evacuation in their secret, to conduct monitoring and ranging on the level of SC goat milk of herds in the Eastern region during 2015 seasonally. Somatic cell count was studied on a large number of animals in different zones of the East of Ukraine (1800 milk samples). Somatic cell count in goat milk of the Eastern region of Ukraine appears up to 800×10³ cells/ml at 65-71% of studied milk samples by the method of laser-running cytometry with the account of only those cells having DNA in the nucleus. While analyze of SC subpopulations in goat milk it is shown that at increase to 2 million cells/ml and more the concentration of neutrophils and lymphocytes does not change and the number of macrophages and eosinophils (р≤0,05) rises from 1,5 to 4 times accordingly. It is marked that SC contents in goat milk in the morning and evening yield of milk is different. In evening yield of milk, the somatic cell count is up to 30 % higher than in the morning one. A clear pattern of distribution of somatic cells in milk portions during milking was not detected. Average sample of yield is required to determine the somatic cell count in the milk of goats. Six of the eight goats over six months of lactation were given milk with a fairly constant somatic cell count. Low and fairly constant somatic cells content (15 to 63 × 103 cells / ml) is observed in the milk of primiparous goats.